2D modelling of a thin elasto-plastic interphase between two different materials: Plane strain case - Mishuris, Gennady (Elsevier, 2007)
A thin soft elasto-plastic interphase between two different media is under consideration. The intermediate layer is assumed to be of infinitesimal thickness and is modelled by non-linear transmission conditions which incorporate the elasto-plastic material behaviour of the layer. FEM analysis of a bimaterial structure with such an imperfect elasto-plastic interface shows the efficiency of the approach and illustrates some restrictions of its application.